Ortodontik interseptif: efektivitas rapid palatal expander pada crowding gigi anterior pada anak Interceptive orthodontics: effectivity of rapid palatatal expander in children withanterior teeth crowding - Harun Achmad; Hendrastuti Handayani (DiscoverSys Inc., 2012)
Interceptive orthodontic treatment aims to reduce and improve the causes of malocclusion in the stage of growth and development that may have a bad effect in the future. Dental crowding is a state of the disproportion betweenthe size of the teeth, jaw size and arch length. There are three conditions that facilitate the crowding, the width ofthe teeth, small jaw basal bones or a combination of both. One of the techniques of handling the case of childrenanterior crowding due to disproportion size of tooth width with a narrow arch is the rapid palatal expander device(RPE) in order to obtain the ideal space for the teeth and arch length. A boy, aged 11 years, wants to be treated histeeth with complaints teeth of front upper jaw and lower jaw experiencing crowding, thereby disrupting theappearance and mastication. Almost all the permanent teeth have erupted, and the jaw is still in its infancy. Thetreatment is carried out with a combination of fixed orthodontic devices and RPE for 4 months of treatment, showed a positive change in the profile seen in clinical oral cavity conditions of patients.